2016
DOI: 10.1139/apnm-2015-0390
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of visual and auditory information to accurately predict the direction and rotational motion of a visual stimulus

Abstract: Vision and auditory information are critical for perception and to enhance the ability of an individual to respond accurately to a stimulus. However, it is unknown whether visual and auditory information contribute differentially to identify the direction and rotational motion of the stimulus. The purpose of this study was to determine the ability of an individual to accurately predict the direction and rotational motion of the stimulus based on visual and auditory information. In this study, we recruited 9 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…In contrast, our findings indicate that the number of correct answers of the sample did not occur by chance, as the number of correct answers (10.2 = 50.9%) was significantly higher than the number that could occur by chance (5 = 25%), considering that the possibility of a correct answer by chance was 1 in the 4 options (flat, slow, medium, fast) in each of the 20 attempts that the participants performed. Some factors may have contributed to the discrepancy between our results and those reported in the study by Park et al (2015 ). First, the strokes used in the studies were not the same.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, our findings indicate that the number of correct answers of the sample did not occur by chance, as the number of correct answers (10.2 = 50.9%) was significantly higher than the number that could occur by chance (5 = 25%), considering that the possibility of a correct answer by chance was 1 in the 4 options (flat, slow, medium, fast) in each of the 20 attempts that the participants performed. Some factors may have contributed to the discrepancy between our results and those reported in the study by Park et al (2015 ). First, the strokes used in the studies were not the same.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors found that after adding auditory information to visual information, the ability of table tennis players to predict the type of spin of a service improved by 15%. However, the previous study presents a contradictory finding to ours, as it indicated that when the table tennis players received only auditory information (with no additional visual information), the ability to predict the direction or spin of a service was not significantly different from chance ( Park et al, 2015 ). In contrast, our findings indicate that the number of correct answers of the sample did not occur by chance, as the number of correct answers (10.2 = 50.9%) was significantly higher than the number that could occur by chance (5 = 25%), considering that the possibility of a correct answer by chance was 1 in the 4 options (flat, slow, medium, fast) in each of the 20 attempts that the participants performed.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This pattern improves with regular training of sports. Such subjects are aptly considered as positively conditioned subjects in the present experiment [10].…”
Section: Occupational Exposurementioning
confidence: 99%